Evidence and determinants of post-abortion family planning utilization among women of reproductive age in Africa: an umbrella review - Kaura, Doreen Kainyu; Demissie, Dereje Bayissa; Gebhardt, Stefan (Frontiers in Reproductive Health, 2025)
BackgroundPost-abortion family planning (PAFP), ideally initiated within 48 h, is crucial for preventing unplanned pregnancies. Repeat-induced abortion remains a significant challenge to the sexual and reproductive health of women. Despite numerous systematic reviews and meta-analyses, inconsistent findings still hinder effective policy formulation and clinical decision-making. In Africa, high rates of unsafe abortion and unintended pregnancy persist, exacerbated by socioeconomic and health system barriers. This umbrella review consolidates global evidence on the prevalence, determinants, and use of PAFP to inform health policy, strengthen service delivery, and promote reproductive health equity, especially in regions with limited access to safe abortion services and contraception.MethodsAn umbrella review of systematic reviews and meta-analyses based on observational studies was conducted. The methodological quality of the included studies was assessed using the Assessment of Multiple Systematic Reviews tool. Heterogeneity was assessed using Cochran's Q and I2 statistics, while publication bias was evaluated using Egger's test and funnel plots. A random-effects meta-analysis was used to estimate the pooled effect size, with analyses performed using Stata version 19. Subgroup analyses were performed by country and continent. Pooled results were synthesized using random-effects meta-analysis models. The review protocol was registered with PROSPERO (CRD420251089314).ResultThis umbrella review included six systematic reviews and meta-analyses, comprising 198 primary studies conducted across 44 African countries, with a combined sample size of 420,832 women of reproductive age assessing post-abortion family planning utilization. This umbrella review found that the pooled prevalence of post-abortion family planning utilization among women of reproductive age in Africa was 62.82% (95% CI: 59.24%–66.40%), indicating substantial uptake but with high heterogeneity across studies (I2 = 98.81%). A subgroup umbrella meta-analysis revealed that the pooled prevalence of post-abortion family planning utilization was 69.31% (95% CI: 64.27%–74.35%) in Ethiopia, compared to 60.29% (95% CI: 57.11%–63.47%) in other African countries. This study determined that injectables were the most commonly utilized post-abortion family planning method (34.12%), followed by pills and implants, each with a nearly equal share of 22%. This umbrella review identified key pooled determinants of post-abortion family planning utilization among women of reproductive age in Africa, including marital status (being married), younger maternal age (15–24 years), educational attainment, receipt of post-abortion family planning counseling, prior use of family planning, history of abortion, unintended pregnancy, and contraceptive knowledge.Conclusion and recommendationThe high prevalence of PAFP utilization in Africa (62.82%), and particularly in Ethiopia (69.31%), reflects encouraging progress. However, the fact that 37.18% of post-abortion women in Africa and 30.69% in Ethiopia still do not use PAFP underscores a critical gap that demands targeted policy action. The predominance of injectable contraceptives highlights the need to expand access to a broader range of methods, including long-acting reversible contraceptives, to support informed and voluntary choice. Policymakers and health planners in Africa should urgently strengthen reproductive health policies by implementing a comprehensive, multipronged strategy to ensure universal access to post-abortion care.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251089314, PROSPERO CRD420251089314.